Analysis of the Influencing Factors of the Acoustic Performance of the Muffler Considering Acoustic-structural Coupling - ZHAO, Bo; LI, He (Archives of Acoustics, 2022)
In the calculation of the acoustic performance of mufflers, the walls of mufflers are usually treated rigidly without considering the acoustic-structural coupling, but the results so calculated differ significantly from the actual situation. Based on the basic equations, the article derives the finite element equations of the muffler system while considering the acoustic-structural coupling effect and theoretically analyses the connection between the acoustic-structural coupling system and the structural and acoustic modes. The structural and acoustic modes of the muffler are calculated and the reasons for the mutation of the transmission loss curve of the muffler when the acoustic-structural coupling is considered are analysed. The results show that the acoustic-structural coupling is the result of the interaction between the structure and the air inside the expansion chamber under acoustic excitation, which manifests mutations in the sound pressure inside the muffler in some frequency bands. Then, using a single-chamber muffler as an example, the transmission loss is used to characterise the performance of the muffler. The effects of different factors such as shell thickness, structure, porous media material lining, and restraint method on the acoustic-structural coupling effect of the muffler are analysed, and the structure of a double-chamber muffler is successfully optimised according to the conclusions.